ANALISIS ELEMEN AIDA PADA MEDIA SOSIAL INSTAGRAM @indonesia.g20 DALAM PRESIDENSI G20 INDONESIA - R. Rifqi Priobagas Putra Wardana; Ni Luh Yulyana Dewi (CV. Lafadz Jaya, 2026)
This study aims to analyze the implementation of AIDA communication elements (Attention, Interest, Desire, Action) on the Instagram account @indonesia.g20 during Indonesia’s G20 Presidency. A qualitative descriptive approach was employed through observation, documentation, and interviews with one expert informant and five followers selected using purposive sampling. The findings indicate that @indonesia.g20 effectively attracted public attention through informative visual content and interactive Instagram features. Audience interest and desire were developed through creative content presentation and transparent information delivery. The action stage was reflected in audience engagement, such as following the account, liking, commenting, and sharing information related to G20 activities. This study concludes that Instagram played an effective role as a digital communication medium in enhancing public engagement during Indonesia’s G20 Presidency.